Desarrollo de un sistema IoT para el monitoreo de variables eléctricas requeridas en Sistema de Gestión Energética. - Bryan Roy, Castillo Yaguana (2024)
This graduation project was carried out in an experimental context with the aim of creating an IoT (Internet of Things) system for recording and visualizing low-voltage electrical variables necessary for the implementation of energy management systems (EMS). The following components were employed: The ZMPT101B sensor, designed to measure alternating current (AC) voltage, utilizes a microcontroller to convert the voltage into a range from 0 V to 5 V, allowing seamless integration into electrical and electronic systems. In addition, a non-invasive YHCD SCT-13 current sensor was used for measuring current intensity without interrupting the electrical circuit, which proves valuable in control and energy monitoring applications. A 20X4 LCD screen displays the values read from the current, voltage, and power sensors. The ESP32 WROOM-32D microcontroller enables Wi-Fi communication and TCP/IP connections for a wide range of applications. All of these components are housed within a white acrylic casing. Communication was established through the Ubidots platform, which facilitates global decision-making, data transmission to the cloud, integration with other platforms, and realtime mapping. Tests were conducted in a residence, capturing electrical consumption patterns. The prototype was installed in the distribution board to monitor current and voltage, calculating power in 5-minute intervals for each connected device. This prototype proves to be invaluable for identifying consumption patterns, creating indicators, and monitoring lowvoltage electrical installations in real-time. Keywords: Energy meters, energy management systems, IoT architecture for electrical variable measurement, energy efficiency, electrical consumption.